ATRIAL FIBRILLATION AS A POSSIBLE CAUSE OF CARDIOVASCULAR COMPLICATIONS - Asror Olimkulovich Lakhanov; Tashkenbaeva Eleonora Negmatovna (Scholar Express Journals, 2024)
Atrial fibrillation (AF) is the most frequent supraventricular arrhythmia (SVA) in humans [1, 2]. In a healthy heart, excitation occurs physiologically through the sinus node as a "beat generator". To date, there are several ways to diagnose FP. Already information in the history and clinical symptoms such as palpitations, fainting, weakness, dyspnea up to the complication of thromboembolic events can lead to a suspected diagnosis. Subsequently or often as an incidental finding, episodes of FP may be diagnosed by manual heart rate monitoring or by electrocardiogram (ECG), long-term ECG, or external or implanted event recorder recording. However, the prevalence is distributed very differently in the community and depends on a wide variety of factors. The frequency of FP is significantly higher in industrialized countries such as the USA than in developing countries. North America has the highest prevalence and Asia-Pacific has the lowest.
Keywords: supraventricular arrhythmia; quality of life